A ficção da história nacional portuguesa em A Ilustre Casa de Ramires - Ricardo Ledesma Alonso (Ler História, 2022)
One of the problems that scholars of the literary production of Eça de Queirós have most assiduously addressed is the reflection on history that he developed in the pages of his novel A Ilustre Casa de Ramires (1900). As is well known, this reflection led the writer to criticize the main forms of representation of the national past in Portugal during the Regeneração: the ultra-romantic historical novel and historicist historiography. This article focuses on an element of this critique that has not been addressed in sufficient detail. Specifically, it examines Eça’s attack on the metaphysical substratum inherent in conventional historical accounts of the Portuguese nation. I argue that A Ilustre Casa de Ramires deserves to be read as a discourse that, through a repertoire of fictional strategies, questioned the historical meta-narrative presupposed by representations of the national past during post-Ultimatum Portugal.